2020
DOI: 10.3892/mmr.2020.11451
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of P110δ promotes the development of myocarditis in ApoE‑deficient mice by increasing mononuclear cell peritoneal infiltration

Abstract: Phosphoinositide 3-kinase catalytic subunit δ isoform (P110δ) is mainly expressed in white blood cells. it is involved in T and B lymphocyte differentiation, maturation and the neutrophil chemotaxis process. apolipoprotein e (apoe) is an arginine-rich alkaline protein, which is present in plasma chylomicron, low-density lipoprotein and very low-density lipoprotein. The present study aimed to determine the effects of P110δ deletion on myocarditis in apoe-/mice. a mouse model of apoe and P110δ double deletion wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
1
0
0
Order By: Relevance
“…Basic research and clinical experiments indicate that the biochemical, morphological, and genetic indices of cardiomyocytes are altered following EA pretreatment, which can activate endogenous mechanisms and resistance against disease damage that may occur in later stages [33]. Our results showed that EA pretreatment reduced the elevation of the ST segment in the ECG, arrhythmia scores, and alteration of the morphology of myocardial cells of MIRI rats, similar to the findings of previous studies [34][35][36][37]. However, the specific mechanism remains to be elucidated.…”
Section: Discussionsupporting
confidence: 89%
“…Basic research and clinical experiments indicate that the biochemical, morphological, and genetic indices of cardiomyocytes are altered following EA pretreatment, which can activate endogenous mechanisms and resistance against disease damage that may occur in later stages [33]. Our results showed that EA pretreatment reduced the elevation of the ST segment in the ECG, arrhythmia scores, and alteration of the morphology of myocardial cells of MIRI rats, similar to the findings of previous studies [34][35][36][37]. However, the specific mechanism remains to be elucidated.…”
Section: Discussionsupporting
confidence: 89%